Structural, magnetic and electrical properties of Y1-xScxFeO3 (x= 0, 0.5 & 1) nanoparticles synthesized by the sol-gel method - Nakhaei, Mehrnoush; Nobre, Marcos A.L. [UNESP]; Khoshnoud, Davoud Sanavi; Bremholm, Martin; Khonakdar, Hossein Ali (Elsevier, 2023)
Nanoparticles exhibiting crystalline and single-phase characteristics with Y1-xScxFeO3 (x = 0, 0.5 & 1) nanoparticles synthesized by sol-gel method. The sizes of nanocrystals determined by X-Ray Diffractometry (XRD) were obtained between 30 and 39 nm. The shape of nanoparticles and the surface morphology of the samples were carried out using Field Emission Scanning Electron Microscopy (FE-SEM) and energy dispersive spectroscopy (EDS). The magnetic properties of Y1-xScxFeO3 samples were investigated by Vibrating Sample Magnetometry (VSM) and Field-Cooled (FC) and Zero-Field-Cooled (ZFC) measurements. The results showed antiferromagnetic and paramagnetic behaviors for these prepared perovskites. The electrical properties of the samples were investigated by measuring the polarization-electric loops, dielectric constant changes and dielectric loss through frequency and temperature. These measurements showed the TN values of the samples to be 628 and 578 K for YFeO3 and ScFeO3 nanoparticles, respectively. In addition, diffuse reflectance spectroscopy analysis was used to calculate the band gap energy of the samples based on the Kubelka-Munk function. The achieved values showed the band gap energy of 2.97 and 3.07 eV for YFeO3 and ScFeO3.
Keywords: Electrical properties; Magnetic properties; Sol-gel; XRD